Is human retina a poorly designed structure? analysis between creationist and evolutionist view - Mohamad, Mohd Yusof; Ithnin, Mohd Hafidz (2022)
Introduction: Human retina is an inverted structure causing the light to travel multiple layers to reach the photoreceptors. Evolutionist scientist assume this a poorly designed structures. It is consider as a scar of past evolution causing the presence of blind spot. In contrast, creationist scientist refuted the idea by proposing necessary visual functions associated with the structure.Methodology: Selected articles and journals from google seached engine were chosen to analysed both view of creationist and evolutionist. Results: Evolutionist views back-wired designed lead to blindspot, detached retina, macular regeneration, angular closure glaucoma, unnecessary extraocular muscles and susceptibility to disease. On other side of coin, creationist view the design is important to avoid degradation of photoreceptors, production of high resolution of image,tolerated blindspot, good visual acuity and a superior space saving solution. Discussion: The structure of human eye demonstrated optimal condition for proper functioning of visual images.No single ultimate structures are free from diseases or deficiencies. The inverted retina structures are not uniquely to human alone. Conclusion: Future studies are needed to unravel the unique structure of human retina.